2015
DOI: 10.1590/s0103-73312015000200016
|View full text |Cite
|
Sign up to set email alerts
|

Elementos que influenciam o acesso à atenção primária na perspectiva dos profissionais e dos usuários de uma rede de serviços de saúde do Recife

Abstract: Resumo: Apesar de todo o arcabouço institucional e do aparato jurídico-legal do SUS criado para melhorar o acesso da população aos serviços de saúde, ainda existem muitas barreiras que interferem na concretização do acesso universal à saúde no Brasil. Objetivamos analisar os elementos que influenciam o acesso aos serviços de atenção primária no município de Recife na perspectiva de profissionais e usuários. Trata-se de um estudo de caso realizado através de entrevistas semiestruturadas com46 informantes. A aná… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
60

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 18 publications
1
26
0
60
Order By: Relevance
“…However, the deviation of the agents´ functions to do activities such as reception in the unit reduces access in that it reduces the time for home visits 6 , as verified in the present research.…”
Section: Acknowledgmentssupporting
confidence: 78%
See 1 more Smart Citation
“…However, the deviation of the agents´ functions to do activities such as reception in the unit reduces access in that it reduces the time for home visits 6 , as verified in the present research.…”
Section: Acknowledgmentssupporting
confidence: 78%
“…Different elements of PHC work are described in the literature in their relation or impact on the guarantee of access to health services, such as: the training of workers 5 ; the organization of the work process 6 and the workload 7 . Also, the norms that guide health practices in daily services, such as working hours and teamwork, depending on how they are used may or may not contribute to increased access.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar dos benefícios próprios da implantação da ESF, necessita-se de priorizar a gestão, para investir na estrutura e melhorar a organização dos serviços da rede de saúde. 20 Na análise múltipla verificou-se que sexo, faixa etária e cor de pele, apesar de associados, na análise bivariada, com a variável dependente "atendimento na primeira vez que procurou por um serviço de saúde pública, nos últimos 15 dias", não permaneceram no modelo múltiplo, demonstrando serem variáveis de confusão. Neste sentido, as características do perfil não influenciaram no acesso aos serviços de saúde.…”
unclassified
“…19 On the other hand, studies have reported that forwarding by the community health agents is a strategy that favored the access to appointments at the services. [20][21] Home care is an alternative care modality for the users' access to the service, guaranteeing the right to care for users who are limited or cannot come to the service. 22 Another strategy is telephone contact, permitting appointment scheduling and access to care in remote areas.…”
mentioning
confidence: 99%